DAMPAK PROGRAM PEMBANGUNAN AIR MINUM DAN PENYEHATAN LINGKUNGAN DI KOTA PAYAKUMBUH - Agnesia, Wina; Frinaldi, Aldri; Candra Gustina, Henni (Humanus, 2014)
This research aims to discover and analyze the effect of the development of drinking water program and environmental health in improving the quality of life in Payakumbuh city. The background of the research is the various environmental problems in Payakumbuh. This research is quantitative as well as descriptive qualitative. The population of the research is the community of Payakumbuh city in five districts. The result shows that the provision of basic sanitary system in Payakumbuh is in medium level. This can be inferred from the data analysis that shows the average basic sanitary level in 3.6 between 1 to 5 and the TCR reaches 63.20%, which means medium category. The waste management of Payakumbuh city is in medium category, where the anticipation of local waste is only 2.85 between 1 to 5 and TCR 57.00%. The drainage facility of Payakumbuh city is in medium category with the score reaching 3.13 between 1 to 5 and the TCR 62.60. The quality of environment in Payakumbuh city is quite good, shown by the score 3.25 between 1 to 5 and TCR 65.00%. This means the environmental quality of the developing city is quite good and within medium category. Therefore, it can be concluded that the development of drinking water program and environmental health contributes to the quality of environment that are proven by the sub-variables; all in medium category.Key words: drinking water, environmental health, sanitary